Publisher correction: Actively personalized vaccination trial for newly diagnosed glioblastoma - Hilf, Norbert; Platten, Michael; Deimling, Andreas von; Capper, David; Wick, Wolfgang; Bunse, Lukas (Nature, 2019)
The additional author support information was erroneously omitted from the Supplementary Information. This has been corrected online.
Gesehen am 15.05.2019